Antimicrobial Activity of some Edible Mushrooms in the Eastern and Southeast Anatolia Region of Turkey - Akyuz, Mehmet; Onganer, Ayse Nilay; Erecevit, Pinar; Kirbag, Sevda (Gazi Univ, 2010)
In this study, the antimicrobial activity of Pleurotus eryngii var. eryngii, P. eryngii var. ferulae, P. ostreatus, P. sajor-caju, Terfezia boudieri and Agaricus bisporus were investigated. The antimicrobial activity from the methyl alcohol extract of Pleurotus spp., T. boudieri and A. bisporus were evaluated according to the disk diffusion method by using Bacillus megaterium, Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Candida albicans, C. glabrata, Trichophyton spp. and Epidermophyton spp. At the end of the experimental studies, the methyl alcohol extracts of Pleurotus spp., T. boudieri and A. bisporus were shown to inhibit to different degrees the growth of microorganisms to (7.5-15.5 mm) also, mushrooms extract have a lower antimicrobial activity as to a comparison antibiotic (13.0-18.0mm).
Keywords: A. bisporus; Antimicrobial Activity; Pathogen Microorganism; Pleurotus spp.; T. boudieri